2023
DOI: 10.1002/ese3.1416
|View full text |Cite
|
Sign up to set email alerts
|

Study on surrounding rock failure mechanism and rational coal pillar width of the gob‐side coal roadway under influence of intense dynamic pressure

Abstract: A reasonable width of the coal pillar is very important to the surrounding rock control of the gob-side roadway. An unreasonable width of the coal pillar will make the roadway to be located within the range of strong mining influence, leading to severe deformation of the roadway. Severe subsidence at the coal pillar side of the roof and serious coal pillar deformation are problems caused by strong dynamic pressure due to mining in the gob-side coal roadway. This paper studies the surrounding rock instability m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Ma et al [15] observed that the effectiveness of U-shaped steel supports in mitigating deformation and damage to roadways under dynamic pressure was limited. Wang et al [16] studied the stress field in a side coal roadway of a goaf under the influence of mining, and they suggested a support scheme that combines "anchor cable + grouting + single pillar". Zhu et al [17] developed a mechanical model to analyze the behavior of rock beams on roadways' floors subjected to dynamic pressure, quantified the displacement when each load acted independently, and proposed a control method of "bottom crane + bottom corner anchor + floor anchor" to control roadways under dynamic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [15] observed that the effectiveness of U-shaped steel supports in mitigating deformation and damage to roadways under dynamic pressure was limited. Wang et al [16] studied the stress field in a side coal roadway of a goaf under the influence of mining, and they suggested a support scheme that combines "anchor cable + grouting + single pillar". Zhu et al [17] developed a mechanical model to analyze the behavior of rock beams on roadways' floors subjected to dynamic pressure, quantified the displacement when each load acted independently, and proposed a control method of "bottom crane + bottom corner anchor + floor anchor" to control roadways under dynamic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the narrow coal pillar stability, control technologies such as rational coal pillar width, 19 roof cutting pressure relief, 20–24 and strengthened support 25 have been proposed. There are also joint applications of multiple technologies 26–28 . In addition, Chen et al 29 proposed filling the goaf to improve the narrow coal pillars stability.…”
Section: Introductionmentioning
confidence: 99%
“…There are also joint applications of multiple technologies. [26][27][28] In addition, Chen et al 29 proposed filling the goaf to improve the narrow coal pillars stability.…”
Section: Introductionmentioning
confidence: 99%
“…Their findings champion the use of high-prestressed strong anchor rods and comprehensive cable supports as effective tools in mitigating deformation in gob-side entry paths. Meanwhile, Wang et al [8] amalgamated various methodologies-from field investigations to laboratory tests, from numerical models to theoretical insights-to discern the inconsistent deformation mechanisms in slim coal pillar pathways. Their research indicates that maintaining a 6 m breadth for coal pillars optimizes outcomes.…”
Section: Introductionmentioning
confidence: 99%